Effects of medium-chain triglyceride ingestion on fuel metabolism and cycling performance - van Zyl, C. G.; Lambert, E. V.; Hawley, J. A.; Noakes, T. D.; Dennis, S. C. (Journal of Applied Physiology, 1996)
On three occasions separated by 10 days, six endurance-trained cyclists rode for 2 h at 60% of peak O2 uptake and then performed a simulated 40-km time trial (T-trial). During the rides, the subjects ingested a total of 2 liters of a [U-14C]glucose-labeled beverage containing a random order of either 10% glucose [carbohydrate (CHO)], 4.3% medium-chain triglycerides (MCTs); or 10% glucose + 4.3% MCTs (CHO+MCT). Although replacing CHO with MCTs slowed the T-trials from 66.8 +/- 0.4 (SE) to 72.1 +/- 0.6 min (P < 0.001), adding MCTs to CHO improved the T-trials from 66.8 +/- 0.4 to 65.1 +/- 0.5 min (P < 0.05). Faster T-trials in the CHO+MCT trial than in the CHO trial were associated with increased final circulating concentrations of free fatty acids (0.58 +/- 0.09 vs. 0.36 +/- 0.06 mmol/l; P < 0.05) and ketones (1.51 +/- 0.25 vs. 0.51 +/- 0.07 mmol/l; P < 0.01) and decreased final circulating concentrations of glucose (5.2 +/- 0.2 vs. 6.3 +/- 0.3 mmol/l; P < 0.01) and lactate (1.9 +/- 0.4 vs. 3.7 +/- 0.5 mmol/l; P < 0.05). Adding MCTs to ingested CHO reduced total CHO oxidation rates from 14 +/- 1 to 10 +/- 1 mmol/min at 2 h and from 17 +/- 1 to 14 +/- 1 mmol/min in the T-trial (P < 0.01), without affecting the corresponding approximately 5 and approximately 7 mmol/min rates of [14C]glucose oxidation. These data suggest that MCT oxidation decreased the direct and/or indirect (via lactate) oxidation of muscle glycogen. A reduced reliance on CHO oxidation at a given O2 uptake is similar to an endurance-training effect, and that may explain the improved T-trial performances.